Upgrading volatile fatty acids production from anaerobic co-fermentation of orange peel waste and sewage sludge: Critical roles of limonene on functional consortia and microbial metabolic traits. (October 2022) - Shao, Qianqi; Zhang, Qin; Fang, Shiyu; Huang, Wenxuan; Li, Ziyu; Fang, Xinyang; Bao, Xingchen; Lin, Lifang; Cao, Jiashun; Luo, Jingyang
Graphical abstract: Highlights: Co-fermentation of OPW and SS is feasible for VFAs promotion. The solubilization and hydrolysis are facilitated but restrain the methanogenesis. The positive roles of limonene on the OPW/SS co-fermentation are elucidated. The functional bacteria for VFAs biosynthesis are significantly enriched. The microbial metabolic traits associated with VFAs generation are unveiled. Abstract: Orange peel waste (OPW) and sewage sludge (SS) valorization for volatile fatty acids (VFAs) production from anaerobic co-fermentation are attractive and feasible. The highest VFAs reached 11996.3 mg COD/L within 10 d at the mass ratio (TS/TS) of 1:1, which was approximately 30-fold of that in sole SS fermentation. The OPW provided plenty of organic substrates and facilitated the fermentation processes by disintegrating SS structure and inhibiting methanogenesis due to the abundant limonene. Also, the OPW feeds reshaped the microbial community and enriched fermentative bacteria, especially those saccharolytic ones ( i.e. Prevotella-7 ). The key genes involved in membrane transport ( i.e. ptsG ), glycolysis ( i.e. pgk ), pyruvate metabolism ( i.e. ace ), and fatty acid biosynthesis ( i.e. accA ), which are associated with VFAs biosynthesis, were up-regulated in OPW/SS reactors. Overall, it was the increase in bioavailable organic matter and functional microorganisms, and the simultaneous enhancement of metabolic activity that improved the efficient VFAs production.